STUDI NASKAH: TEKS-TEKS KLASIK PENDIDIKAN ISLAM - T. Hasballah; Tarmizi Ninoersy (CV. ADIBA ASIHA AMIRA, 2025)
This research discusses the classical texts of Islamic education which includes a study of the works of scholars who form the basis of educational theory and practice in the Islamic tradition. The formulation of the problem of this research is how the classical texts of Islamic education influence the development of Islamic education until today. The purpose of this research is to explore the meaning and relevance of these texts in the formation of a modern Islamic education system. This research uses the literature study method by analysing primary and secondary sources. The results show that the classical texts of Islamic education provide an important foundation in the preparation of the curriculum and values of Islamic education until today.